Membangun Kebiasaan Sehat Untuk Atlet Remaja Di SMAN 6 Kota Gorontalo - Zikra, Moh; Arriski, Muh Hafidz; Darise, Rifki; Pakaya, Wajrianto J; Hasana, Jesi S; Nauko, Ali; Madnun, Syahrdiansyah; Tangahu, Ronaldi; Paputungan, Moh Rizki; Tangahu, Aril; Haryani, Meri; Irawan, Safri (-, 2025)
This community service activity aims to educate about healthy eating habits and the importance of sufficient sleep for teenagers, particularly athletes, at SMAN 6 Gorontalo. In this activity, an interactive and enjoyable approach was applied to help students understand the importance of healthy habits in supporting their physical and mental health. The methods used include step-by-step material delivery, group discussions, and light games to warm up the atmosphere. The evaluation of the activity shows that students were enthusiastic and actively participated, as well as demonstrating readiness to apply healthy eating habits and improve their sleep quality. The success of this activity is not only reflected in achieving the learning objectives but also provides valuable experience for the team in designing and implementing effective and enjoyable educational activities. These results highlight the importance of community service efforts in educating teenagers about healthy lifestyle habits that can improve their quality of life